Prisma pemikiran Gus Dur - Wahid, Abdurrahman, 1940- (Yogyakarta : LKiS, 2000)
Socioeconomic, political, and religious issues in Indonesia; collection of articles previously published in Prisma journal
Keywords: Islam and politics -- Indonesia; Indonesia -- Politics and government